Targeting ryanodine receptors for anti-arrhythmic therapy - McCauley Mark D; Wehrens Xander H T (Acta Pharmacologica Sinica, 2016)
Antiarrhythmic drugs are a group of pharmaceuticals that suppress or prevent abnormal heart rhythms, which are often associated with substantial morbidity and mortality. Current antiarrhythmic drugs that typically target plasma membrane ion channels have limited clinical success and in some cases have been described as being pro-arrhythmic. However, recent studies suggest that pathological release of calcium (Ca2+) from the sarcoplasmic reticulum via cardiac ryanodine receptors (RyR2) could represent a promising target for antiarrhythmic therapy. Diastolic SR Ca2+ release has been linked to arrhythmogenesis in both the inherited arrhythmia syndrome 'catecholaminergic polymorphic ventricular tachycardia' and acquired forms of heart disease (eg, atrial fibrillation, heart failure). Several classes of pharmaceuticals have been shown to reduce abnormal RyR2 activity and may confer protection against triggered arrhythmias through reduction of SR Ca2+ leak. In this review, we will evaluate the current pharmacological methods for stabilizing RyR2 and suggest treatment modalities based on current evidence of molecular mechanisms.